2021
DOI: 10.3389/fmed.2021.776955
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii Combined With Quadruple Therapy for Helicobacter pylori Eradication Decreased the Duration and Severity of Diarrhea: A Multi-Center Prospective Randomized Controlled Trial

Abstract: Background: Whether probiotics helped the Helicobacter pylori (H. pylori) eradication was still highly controversial. The non-bacterial Saccharomyces boulardii (S. boulardii) has demonstrated its efficacy in the treatment of antibiotic-associated and infectious diarrhea. We aimed to evaluate the effects of S. boulardii combined with quadruple therapy for H. pylori eradication and associated side effects.Methods: Three hundred and sixty H. pylori-infected patients were recruited in this multicenter, randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
2
16
0
1
Order By: Relevance
“…We observed no difference between probiotics and placebo group in eradication rate, both of which achieved up to 90% as revealed by PP analysis. Additionally, we found that probiotics combination mitigated gastrointestinal adverse events induced by eradication therapy, which is in agreement with other studies ( 10 , 12 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed no difference between probiotics and placebo group in eradication rate, both of which achieved up to 90% as revealed by PP analysis. Additionally, we found that probiotics combination mitigated gastrointestinal adverse events induced by eradication therapy, which is in agreement with other studies ( 10 , 12 ).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a large number of studies explored the efficacy of adjuvant probiotics therapy for patients with H. pylori infection, yet the clinical outcomes were controversial ( 3 ). While some studies reported improved eradication rate in patients given probiotics, others showed negative results ( 10 , 22 ). We observed no difference between probiotics and placebo group in eradication rate, both of which achieved up to 90% as revealed by PP analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yu et al proposed adding S. boulardii to quadruple therapy, which relieved H. pylori eradication - induced antibiotic-associated side effects but did not improve the eradication rate of H. pylori. 19 Based on the outcomes of current studies, S. boulardii did reduce treatment-associated side effects for H. pylori eradication, especially gastrointestinal symptoms, but whether S. boulardii could improve the eradication rate of 14-day quadruple therapy for H. pylori was still lack of adequate evidence and has to be discussed further, just as what the guidelines have mentioned. In this study, we aimed to demonstrate the efficacy and safety of S. boulardii supplementation on antofloxacin-based bismuth quadruple therapy for H. pylori eradication.…”
Section: Introductionmentioning
confidence: 89%
“…Two meta-analyses have shown that the supplementation with S. boulardii in the standard triple therapy can increased the eradication rate of H. pylori and reduced the incidence of overall side effects ( Szajewska et al., 2010 ; Szajewska et al., 2015 ). However, several studies have reported that treatment with S. boulardii combined with the bismuth quadruple can reduce side effects in patients, but fails to further improve eradication rates ( Chen et al., 2018 ; Zhao et al., 2021 ; Naghibzadeh et al., 2022 ). In addition, treatment of H. pylori infection with probiotic monotherapy in children has an eradicate 29.3% of cases ( Boonyaritichaikij et al., 2009 ), While treatment with S.boulardii alone has an eradication rate of 11.8% ( Gotteland et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%